Hubungan Perawatan Payudara dengan Kejadian Bendungan ASI PMB Bella Setiani Kab. Sumatera Selatan Tahun 2023 - Bella Setiani; Lisdayanti Simanjuntak; Lasria Simamora; Basaria Manurung; Dina Afriani (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
According to WHO (2019) the health status of a woman can be determined from the number of deaths due to pregnancy, childbirth and postpartum. The maternal mortality rate is one of the global targets of the Sustainable Development Goals (SDGs) in reducing maternal mortality. Based on the Central Statistics Agency (BPS) in 2023 in South Sumatra Regency, the coverage of exclusive breastfeeding with the percentage of children receiving exclusive breastfeeding from year to year has increased significantly. In 2020 it was 68.06%, in 2021 it was 69.93%, and in 2022 it was 70.46%. Research Method: The type of research used is descriptive analytical research with a cross-sectional research design, namely a method of data collection carried out at the same time. Research Results: Postpartum mothers who experienced breast milk engorgement were 56.3% and only 43.7% did not experience breast milk engorgement. Mothers who do breast care are mostly in the poor category (62.5%) and a few in the good category (37.5%). There is a relationship between Breast Care and the Incident of Breast Milk Dams Conclusion: There is a relationship between Breast Care and the Incident of Breast Milk Dams in Postpartum Mothers